PEMANFAATAN UDARA BUANG EXHAUST FAN UNTUK PEMBANGKIT LISTRIK TENAGA BAYU DENGAN PENGARUH PENAMBAHAN HONEYCOMB BERBASIS ATMEGA 2560 - Kusuma Wardhana, Yoga; Indra Partha, Cok Gede; Sukerayasa, I Wayan (Jurnal SPEKTRUM, 2021)
Energy needs are increasing from year to year in line with the increasing population, economic growth, and high energy consumption. More than 86% of the world's energy today comes from fossil fuels, while the world's energy demand is increasing. One of the considerations for overcoming pollution caused by fossil fuels is to seek alternative energy systems. More than 90% of the energy that affects greenhouse gas emissions is the result of burning fuels globally. Exhaust Fan is a good system for wind power extraction. This air exhaust system is suitable for power plants with wind turbines as a drive where the resulting wind speed is higher and consistent when compared to natural wind, but has turbulent characteristics. This wind is not good for the wind turbine. A honeycomb is a tool used to reduce this turbulent characteristic. The results obtained by the addition of a hexa type Honeycomb to the exhaust fan with a speed of 6m/s using a savonius type turbine, there was a decrease in turbine speed which was previously unstable between 952 to 1007 rpm to 866 rpm and the generator output power decreased by 0.3 watts. The addition of Honeycomb makes the turbine rotate speed stable at 866 rpm and the wind flow becomes laminar.